2018
DOI: 10.1097/adm.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

The More Things Change: Buprenorphine/naloxone Diversion Continues While Treatment Remains Inaccessible

Abstract: The use of diverted/buprenorphine remains common among people who use opioids non-medically and indicates a severe shortage in treatment capacity and inaccessibility of existing services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 22 publications
(27 reference statements)
3
45
1
Order By: Relevance
“…National data from 2018 indicated that only 42 % of substance use treatment facilities offered medications for OUD ( U.S. Substance Abuse and Mental Health Services Administration, 2019 ). As well, significant waitlists for buprenorphine providers continue to block access to such medications across the U.S. ( Carroll et al, 2018b ; Fox et al, 2015 ; Parran et al, 2017 ). Given these ongoing challenges in the larger healthcare system, it is reasonable to hypothesize that first responders are recognizing (and emotionally responding to) the population effects of insufficient treatment capacity in their own line of work.…”
Section: Discussionmentioning
confidence: 99%
“…National data from 2018 indicated that only 42 % of substance use treatment facilities offered medications for OUD ( U.S. Substance Abuse and Mental Health Services Administration, 2019 ). As well, significant waitlists for buprenorphine providers continue to block access to such medications across the U.S. ( Carroll et al, 2018b ; Fox et al, 2015 ; Parran et al, 2017 ). Given these ongoing challenges in the larger healthcare system, it is reasonable to hypothesize that first responders are recognizing (and emotionally responding to) the population effects of insufficient treatment capacity in their own line of work.…”
Section: Discussionmentioning
confidence: 99%
“…Inaccessibility may force heroin-dependent patients who require prescription methadone, but are unable to consistently visit these centers, to purchase it illicitly ( Carroll, Rich & Green, 2018 ). In Israel, OMT and in-patient centers are usually located in industrial areas in the periphery of cities with limited hours of operation.…”
Section: Discussionmentioning
confidence: 99%
“…These medications (e.g. buprenorphine, methadone) may be misused either alone or in combination with other drugs, to attain euphoria and/or reduce cravings or withdrawal symptoms induced by opioids [ 21 24 ]. Literature reviews have shown that the burden of diversion and misuse of opioid substitution medications includes poor adherence to recommended treatment which negatively impacts treatment outcomes, excess of mortality, somatic complications associated with injecting drug use (e.g.…”
Section: Introductionmentioning
confidence: 99%